Socket preservation using bovine bone with and without dental implant placement - Al Qabbani , Ali Abdul Qader Hameed (2017)
The aim of this interventional study was to assess healing, evaluate bone dimension and the resorption rate of the extraction alveolar socket using bovine bone with and without dental implant placementamong the treated and non-treated tooth extraction sockets. The goal of these approaches was to preserve or minimize the ridge volume loss following tooth extraction by ridge augmentation procedures. The study also evaluates the degree of osseointegration between the immediate implant surface and the alveolar bone.This interventional study was carried out on 30 patients at the University Dental Hospital Sharjah, Sharjah, United Arab Emirates. The patients aged between 18 and 40 years, who needed non-complicated tooth extraction of only one or both mandibular premolar teeth, and being fit and healthy, were included. The project has been approved by UOS and USM ethical committees, and informed consent was obtained. Patients were randomly divided into three groups. In group I, simple extraction was done and the empty extraction socket left untreated and allowed to heal in a conventional way. In group II, extraction sockets were filled with freezedried bovine bone xenograft (FDBBX) granules of size 1mm. A resorbable pericardium membrane was placed to cover the defect to secure the bone granules within the socket and wound closure done with Vicryl suture. In group III, atraumatic extraction was done and an immediate implant placed into the sockets, and the circumferential gap was also filled with FDBBX bone granules and covered with pericardium membrane. This group was additionally subjected to resonance frequency analysis (RFA) by employing Osstell machine for measuring and evaluating the degree of secondary stability at nine months.The patients were followed-up clinically for healing assessment at 1 week, 3 months and 9 months post-operatively (PO). All groups were subjected to cone beam computed tomography scan (CBCT) for radiological evaluation immediately after the surgical procedure at three months and nine months intervals using Sirona Dental Systems, GALILEOS SIDEXIS. CBCT was performed in three different views; coronal, sagittal and axial which involve linear measurements of the socket alveolar bone. RFA was recorded for group III at nine months. There were no clinical differences in healing between the groups. Significant difference of bone resorption was evident in alveolar ridge width and height reduction within control group I, 1.84 mm (Confidence Interval (CI) 95%, 0.57 to 3.10) and 1.91 mm (CI 95%, 0.64 to 3.14) respectively at the intervals of day 0 to nine months. No significant alveolar bone resorption was observed within group II and III. Comparison between group I and III showed a highly significant difference of bone resorption in ridge width at three months 2.56 mm (CI 95%, 4.22 to 0.90) p≤0.001, and at nine months interval 3.2 mm (CI95%, 4.70 to 1.62). Between group II and III, there was a significant difference of bone resorption in ridge width of 1.9 mm (CI95%, 3.43 to 0.34) (p≤0.001). There was no significant vertical ridge resorption observed among the groups. High RFA values were observed in group III at nine months postoperatively. The insertion of immediate implants in fresh extraction sockets together with grafting the circumferential gap between the bony socket wall and the implant surface with bovine bone granules were able to preserve a greater amount of alveolar ridge volume when compared to leaving an extraction socket to heal alone in the conventional way or socket preservation with bovine bone graft only. The periimplant new bone formation developed is of superior quality which led to successful osseointegration between the implant surface and inner surface of the buccal plate. We observed clinically that the USM manufactured FDBBX has completely resorbed and replaced by new bone in the area between the implant and the inner surface of the buccal plate in group III at nine months post-operative.